The Structure of Tweets About Vaccine Safety Between Health Organizations, Experts, and the Public: Analyzing Risk Communication Conversations. (22nd June 2022) - Manheim, David; Gesser-Edelsburg, Anat
Abstract: Objective: This article considers how health education organizations in the World Health Organization's 9 Vaccine Safety Network (VSN) use Twitter to communicate about vaccines with the public, and whether they answer questions and engage in conversations. Almost no research in public health, to our knowledge, has explored conversational structure on social media among posts sent by different accounts. Methods: Starting with 1, 017, 176 tweets by relevant users, we constructed 2 corpuses of multi-tweet conversations. The first was 1, 814 conversations that included VSN members directly, whereas the second was 2, 283 conversations mentioning vaccines or vaccine denialism. The tweets and user metadata were then analyzed using an adaptation of rhetorical structure theory. Results: In the studied data, VSN members tweeted 12, 677 times within conversations, compared to their 37, 587 lone tweets. Their conversations were shorter than those in the comparison corpus (P < 0.0001), and they were involved in fewer multilogues (P < 0.0001). Conclusion: While there is diversity among organizations, most were tied to the pre-social media broadcast model. In the future, they should try to converse more, rather than tweet more, and embrace best practices in risk communication.